Sheep Urine Liquid Organic Fertilizer Improved Oil Palm Seedling Growth - Sitinjak, Rama Riana; Pratomo, Bayu (PLANTA TROPIKA, 2026)
Sheep urine-based liquid organic fertilizer (LOF) offers a low-cost alternative to synthetic fertilizers in oil palm nurseries, yet its application remains limited. Liquid organic fertilizer derived from sheep urine is very effective in increasing seedling growth in the pre-nursery. This study aims to determine the implementation of Liquid organic fertilizer (LOF) sheep urine on the growth of oil palm seedlings in the pre-nursery. A randomized block design was used with four LOF concentrations: N0 = 0 mL/L, N1 = 50 mL/L, N2 = 150 mL/L, and N3 = 300 mL/L. Data were analyzed using analysis of variance, followed by Tukey’s test at the 5% significance level. The results showed that giving LOF from sheep urine could significantly increase the growth of oil palm seedlings, which included seedlings height, stem diameter, number of leaves, fresh weight and canopy dry weight but not for fresh weight and root dry weight of seedlings pre-nursery. The best growth of oil palm seedlings was observed with the application of a liquid organic fertilizer made from sheep urine at a concentration of 300 ml/L at 12 weeks after planting.